Persistent vomiting and failure to thrive as manifestation of achlasia cardia in a chid: a case report - Banoo, Nargis; Hussain, Manzoor (International Journal of Contemporary Pediatrics, 2022)
Achlasia cardia is rare in paaediatric age group, here we present an 18 months old child with recurrent episodes of non bilious vomiting since 12 month of age and failure to thrive. Diagnosis was made on the basis of barium oesophagogram and endoscopic pneumatic dilatation was done which resulted in significant improvement in symptoms.